“Questa fotografia non s’ha da fare…”: Morris Moore, Raffaello e l’Accademia di Belle Arti di Venezia - Filippin, Sara (Rivista di studi di fotografia. Journal of Studies in Photography, 2015)
This paper considers the 1850s controversy involving antiquarian and collector Morris Moore, a drawing of Apollo and Marsyas then at the Academy of Fine Arts in Venice, and a now-lost photograph reproducing it, which in 1857 caused the enactment of the first decree banning photographers from the Gallerie. Focusing on the analysis of a variant print in relation to new archival documents and the original drawing, this study offers a new reconstruction of the facts from a historical and a technical point of view.